2018
DOI: 10.18311/jeoh/2018/20928
|View full text |Cite
|
Sign up to set email alerts
|

Academic Burnout and Some Related Factors in Medical Students

Abstract: Background and Aim: Academic burnout is the feeling of inadequacy and mental fatigue induced by chronic stress in students lacking the necessary resources to carry out their duties and tasks assigned to them. This study aimed to determine academic burnout and some related factors in medical students of Islamic Azad University of Mashhad in 2015-2016. Materials and Methods: In this cross-sectional study, 181 medical students in degrees of basic sciences, traineeship, and internship were selected by convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
2
5
1
1
Order By: Relevance
“…The other benefits like getting hygienic food, good living conditions and people to take care of one's health would have been best when family members were around. The observations in this study were however contradicting the observation of Mostafavian et al (2018) who observed that the academic stress was significantly more among those living at their houses compared to those at dormitories. As many as 60% participants regretted having wasted time set apart for their studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The other benefits like getting hygienic food, good living conditions and people to take care of one's health would have been best when family members were around. The observations in this study were however contradicting the observation of Mostafavian et al (2018) who observed that the academic stress was significantly more among those living at their houses compared to those at dormitories. As many as 60% participants regretted having wasted time set apart for their studies.…”
Section: Discussioncontrasting
confidence: 99%
“…From these comparisons, it was obvious that academic stress was high among the participants in this study probably because of cultural factors. There was no association between academic stress and gender of participants in this study as also reported by Mostafavian et al (2018) and Zamroni et al (2018). However several other studies done among university students reported females to have significantly greater academic stress than males (Adiele et al 2018;Bamuhair et al 2015;Reddy et al 2018;Al-Sowygh et al 2013).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations